Leg Length Discrepancy After Total HIP Replacement - Ahmad, Waqar; Mehmood, Ijaz; Anjum, Ihtesham; Ahmed, Altaf (Indus Journal of Bioscience Research, 2025)
Background: Discrepancy of lower limb length after total hip arthroplasty is a frequent complication that potentially affects postoperative success. Although a number of studies have reported on factors that affect LLD, gender and preoperative factors are yet to be explored. Precise diagnosis and control of LLD are essential for facilitating successful patient recovery and preventing functional impairment. Objective: To determine the frequency of leg length discrepancy after total hip replacement at Khyber Teaching Hospital, Peshawar. Study Design: Descriptive study. Duration and Place of Study: The study was conducted from April 1st to October 1st, 2021, at the Orthopedics Department, Khyber Teaching Hospital (KTH), Peshawar. Methodology: A total of 131 participants aged 60-80 years, scheduled for unilateral total hip arthroplasty, were enrolled using a non-probability consecutive sampling method. Preoperative limb length measurements and demographic data were recorded. Postoperatively, limb length discrepancies were evaluated at one and three months using orthoroentgenogram imaging. Statistical analysis was performed using IBM SPSS version 23, with associations between limb length status and demographic factors assessed through chi-square tests. Results: The mean age of participants was 66.42 ± 4.69 years. Of the patients, 43.5% had a long limb, 20.6% had a short limb, and 35.9% had no discrepancy. Gender was significantly associated with short limb status, with 45.3% of females experiencing a short limb compared to 3.8% of males (p=0.000). No significant associations were found between age, ASA grade, and limb length status. Conclusion: Limb length discrepancy following total hip arthroplasty remains a common issue, with gender identified as a significant factor influencing the occurrence of short limbs.